The art of the Pharaohs - Ferrero, Giorgio (<<The>> American Univ. in Cairo Press, 2010)
This large-format, magnificently illustrated book shows the portraits and monuments that are the artistic masterpiece of antiquity in a new light . It traces the profiles of 34 Kings and queens to present an in-depth picture of the history and art of ancient Egypt and its pharaohs
Keywords: Pharaohs in art; Sculpture / Catalogs; Sculpture, Ancient; Sculpture, Egyptian; Katalog